Real-World Experience of Bevacizumab as First-Line Treatment for Ovarian Cancer: The GINECO ENCOURAGE Cohort of 468 French Patients - Dominique Berton; Anne Floquet; Willy Lescaut; Gabriel Baron; Marie-Christine Kaminsky; Philippe Toussaint; Rémy Largillier; Aude-Marie Savoye; Jérôme Alexandre; Catherine Delbaldo; Emmanuelle Malaurie; Hugues Barletta; et al. (Frontiers Media S.A., 2021)
Introduction: Bevacizumab-containing therapy is considered a standard-of-care front-line option for stage IIIB-IV ovarian cancer based on results of randomized phase 3 trials. The multicenter non-interventional ENCOURAGE prospective cohort study assessed treatment administration and outcomes in the French real-world setting.Patients and Methods: Eligible patients were aged ≥ 18 years with planned bevacizumab-containing therapy for newly diagnosed ovarian cancer. The primary objective was to assess the safety profile of front-line bevacizumab in routine clinical practice; secondary objectives were to describe patient characteristics, indications/contraindications for bevacizumab, treatment regimens and co-medications, follow-up and monitoring, progression-free survival, and treatment at recurrence. In this non-interventional study, treatment was administered as chosen by the investigator and participation in the trial had no influence on the management of the disease.Results: Of 1,290 patients screened between April 2013 and February 2015, 468 were eligible. Most patients (86%) received bevacizumab 15 mg/kg every 3 weeks or equivalent, typically with carboplatin (99%) and paclitaxel (98%). The median duration of bevacizumab was 12.2 (range 0-28, interquartile range 6.9-14.9) months; 8% of patients discontinued bevacizumab because of toxicity. The most common adverse events were hypertension (38% of patients), fatigue (35%), and bleeding (32%). There were no treatment-related deaths. Most physicians (90%) reported blood pressure measurement immediately before each bevacizumab infusion and almost all (97%) reported monitoring for proteinuria before each bevacizumab infusion. Median progression-free survival was 17.4 (95% CI, 16.4-19.1) months. The 3-year overall survival rate was 62% (95% CI, 58-67%). The most commonly administered chemotherapies at recurrence were carboplatin and pegylated liposomal doxorubicin.Discussion: Clinical outcomes and tolerability with bevacizumab in this real-life setting are consistent with randomized trial results, notwithstanding differences in the treated patient population and treatment schedule.Clinical Trial Registration:ClinicalTrials.gov, Identifier NCT01832415.